2008
DOI: 10.1590/s0104-11692008000300006
|View full text |Cite
|
Sign up to set email alerts
|

Personal and interpersonal risk factors in the consumption of illicit drugs by marginal adolescents and young people from juvenile gangs

Abstract: FACTORES DE RIESGO PERSONALES E INTERPERSONALES EN EL CONSUMO DROGAS ILÍCITAS EN ADOLESCENTES Y JÓVENES MARGINALES DE BANDAS JUVENILES FATORES DE RISCO PESSOAIS E INTERPESSOAIS NO CONSUMO DE DROGAS ILÍCITAS EM ADOLESCENTES E JOVENS MARGINAIS DE BANDOS JUVENIS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
(17 reference statements)
2
6
0
3
Order By: Relevance
“…Although the scientific literature had discussed harms caused by the use of PAS (10)(11)(12) ,studies about the use of those and QL have been conducted internationally, majorly between users of injectable drugs, opioids and/or in substitution programs (methadone), noting that the use affects QL, with more losses to emotional, mental health and social functioning aspects (3)(4)13) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the scientific literature had discussed harms caused by the use of PAS (10)(11)(12) ,studies about the use of those and QL have been conducted internationally, majorly between users of injectable drugs, opioids and/or in substitution programs (methadone), noting that the use affects QL, with more losses to emotional, mental health and social functioning aspects (3)(4)13) .…”
Section: Introductionmentioning
confidence: 99%
“…Considering that chemical dependence brings innumerous losses in all life spheres of an individual (10)(11) , that the presence of a comorbidity, as depression, can aggravate and make it difficult the recovery process, affecting directly the quality of life and, still, that there is lack of data about the theme in the mid-west region, we believe that results can contribute to the improvement of political strategies directed to attend this population, aiming a higher adherence to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A convivência com pares engajados em comportamento de risco tem sido vista como fator associado ao envolvimento desse tipo de comportamento durante a adolescência (WANG et al, 2010;EPSTEIN;BANG;BOTVIN, 2007;FACUNDO;PEDRÃO, 2008). Nesse sentido, pesquisas indicam clara correlação entre o consumo de alcoól e ter amigos usuários de álcool e outras drogas (EPSTEIN; BANG; BOTVIN, 2007;FACUNDO;PEDRÃO, 2008). Assim, o fato de ter amigos e familiares usuários de drogas pode ser um fator de risco para o uso dessas substâncias durante a adolescência (KOKKEVI et al, 2007;RAPHAELLI;AZEVEDO;HALLAL, 2011).…”
Section: Risk Behavior In Adolescence: a Systematic Review Of The Natunclassified
“…Quanto à faixa etária, estudos sugerem que adolescentes mais velhos, com 18 ou 19 anos de idade, são mais propensos a se engajar em comportamento de risco do que os mais novos (com 11 ou 12 anos de idade) (FLORENZANO et al, 2009;FACUNDO;PEDRÃO, 2008;FERGUS;ZIMMERMAN;CALDWELL, 2007;ZAPPE;DELL'AGLIO, 2016). O fato de os adolescentes mais velhos adotarem mais comportamentos de risco pode estar relacionado com a crescente conquista de autonomia e de independência.…”
Section: Risk Behavior In Adolescence: a Systematic Review Of The Natunclassified
“…Causes of addiction may stem from cultural, sociodemographic, social and personal factors (Hudak, 1993;Fergusson et al, 1995;McGee et al, 2000;Ibáñez et al, 2001;Orford, 2001;Sussman and Ames, 2001;Harford, 2003; Moewaka Barnes et al, 2003;Clarke, 2005). A descriptive study by Facundo and Pedrão (2008) analysed the personal and interpersonal risk factors of drug consumption among 175 marginal adolescents and young adults who were members of juvenile gangs in Mexico. The study reported that factors such as gender, age, mental health problems, relationships with friends with maladaptive behaviours and poor relationships with parents were associated with higher rates of drug consumption.…”
mentioning
confidence: 99%